2002
DOI: 10.1097/00001756-200212200-00035
|View full text |Cite
|
Sign up to set email alerts
|

Phasic visual alertness in Alzheimerʼs disease and ageing

Abstract: An individual's ability to see and react quickly to a target stimulus is enhanced if they are alerted to the arrival of this target by a stimulus that occurs just prior in time to it. This alerting effect is thought to occur due to a phasic increase in alertness mediated by noradrenergic activity. In Alzheimer's disease (AD) there is a dysfunction in the noradrenergic system resulting in a decrease in central levels of noradrenaline. We therefore predicted that patients with AD would not be able to benefit fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
1
27
1
Order By: Relevance
“…Overall, when presented with more than one pair of bilateral sensory inputs (e.g., somatosensory pulses with concurrent visual asterisks), both age groups demonstrated multisensory alerting effects that were not facilitative and not comparable to those previously described using unisensory visual alerting cues (Fernandez-Duque and Black, 2006; Mahoney et al, 2010; Tales et al, 2002). Interestingly, this phenomenon occurred regardless of chronological age, implying that the effect cannot solely be explained by healthy aging.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Overall, when presented with more than one pair of bilateral sensory inputs (e.g., somatosensory pulses with concurrent visual asterisks), both age groups demonstrated multisensory alerting effects that were not facilitative and not comparable to those previously described using unisensory visual alerting cues (Fernandez-Duque and Black, 2006; Mahoney et al, 2010; Tales et al, 2002). Interestingly, this phenomenon occurred regardless of chronological age, implying that the effect cannot solely be explained by healthy aging.…”
Section: Discussionmentioning
confidence: 57%
“…Tales et al (2002) used a reaction time task with visual alerting cues and reported comparable benefits of alerting in both young and old groups. Similarly, intact phasic alerting in healthy aging and in Alzheimer’s disease (AD) patients was found using a choice RT task with alerting cues (Nebes and Brady, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…We consider the future development of the visual optimal paradigm for the vMMN measurement truly promising as this would considerably facilitate its clinical implementation. Clinically applicable and standardized multi-feature vMMN experiments would be very welcome for diagnostic and treatment-monitoring purposes, for example in the case of Alzheimer’s disease and mild cognitive impairment (e.g., Tanaka et al, 2001; Tales et al, 2002,2008; Tales and Butler, 2006), schizophrenia (Urban et al, 2008) and alcohol intoxication (Kenemans et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that the (v)MMN has clinical value (e.g., Tanaka et al, 2001; Horimoto et al, 2002; Tales et al, 2002,2008; Lorenzo-López et al, 2004; Tales and Butler, 2006; Hosák et al, 2008; Urban et al, 2008; Kenemans et al, 2010; all recently reviewed together with MMN studies by Näätänen et al, 2011,2012), it certainly calls for rigorous and standardized measurement procedures. Furthermore, a systematic look at this clinical work also reveals the same important discrepancy (i.e., difficulties in controlling one’s attention) between auditory and visual MMNs.…”
Section: Introductionmentioning
confidence: 99%
“…Phasic alertness is typically examined by comparing performance with warning signals and without warning signals. Previous studies show that aging has relatively little effect on phasic alertness (e.g., Rabbitt, 1984; Nebes and Brady, 1993; Tales et al, 2002a) when the stimulus onset asynchrony (SOA) between the warning signal and the target was fixed. However, when SOA was varied within a block, Festa-Martino et al (2004) reported that older adults showed smaller alerting effects than younger adults.…”
Section: Introductionmentioning
confidence: 99%